Ruang Lingkup Perbankan dan Lembaga Keuangan di Indonesia - Prety Aulya; Dea Windia; Karina Seftianti; Dewi Malinda Salsabila; Husni Mubarok (CV. Denasya Smart Publisher, 2025)
This research examines the breadth of Indonesia's banking sector and financial service providers, focusing on their contributions to national economic development. The research methodology employed involves comprehensive literature review through examination of pertinent academic and industry sources related to Indonesia's traditional banking sector. The findings reveal that Indonesia's financial banking framework comprises two primary segments: traditional commercial banks and Shariah-compliant banking institutions, distinguished by their core operating philosophies, profit-sharing mechanisms, and regulatory oversight structures. Shariah-based banking has demonstrated remarkable expansion, achieving approximately 15% annual asset growth rates, indicating growing consumer confidence and market acceptance. Indonesia's financial service landscape encompasses two distinct categories: Banking Financial Service Providers (LKB) and Non-Banking Financial Service Providers (LKBB), where each category fulfills essential functions in facilitating financial intermediation processes. The digital revolution has fundamentally transformed financial service delivery models, promoting greater financial inclusion and accessibility across diverse population segments. The research findings indicate that effective collaboration among different categories of financial institutions is crucial for maintaining overall financial system stability while fostering sustainable national economic expansion.